A High-Affinity Monoclonal Antibody Against the Pancreatic Ductal Adenocarcinoma Target, Anterior Gradient-2 (AGR2/PDIA17) - Reeder M. Robinson; Leticia Reyes; Benjamin N. Christopher; Ravyn M. Duncan; Rachel A. Burge; Julie Siegel; Patrick Nasarre; Pingping Wang; John P. O’Bryan; G. Aaron Hobbs; Nancy Klauber-DeMore; Nathan G. Dolloff (Antibodies)
Background/Objectives: Anterior Gradient-2 (AGR2/PDIA17) is a member of the protein disulfide isomerase (PDI) family of oxidoreductases. AGR2 is up-regulated in several solid tumors, including pancreatic ductal adenocarcinoma (PDAC). Given the dire need for new therapeutic options for PDAC patients, we investigated the expression and function of AGR2 in PDAC and developed a novel series of affinity-matured AGR2-specific single-chain variable fragments (scFvs) and monoclonal antibodies. Results: We found that AGR2 was expressed in approximately 90% of PDAC but not normal pancreas biopsies, and the level of AGR2 expression correlated with increasing disease stage. AGR2 expression was inversely related to SMAD4 status in PDAC and colorectal cancer cell models and was secreted from cells into their media. In normal tissues, a high density of AGR2 was detected in the epithelium of cells in the digestive tract but was lacking in most other normal tissue systems. The addition of recombinant AGR2 to cell culture and genetic overexpression of AGR2 increased the adhesion, motility, and invasiveness of both human and mouse PDAC cells. Human phage display library screening led to the discovery of multiple AGR2-specific scFv clones that were affinity-matured to produce monoclonal antibody (MAb) clones with low picomolar binding affinity (S31R/A53F/Y). These high-affinity MAbs inhibited AGR2-mediated cell adhesion, migration, and binding to LYPD3, which is a putative cell surface binding partner of AGR2. Conclusions: Our study provides novel, high-affinity, fully human, anti-AGR2 MAbs that neutralize the pro-tumor effects of extracellular AGR2 in PDAC.